MUKADDES EMANETLERİN İSTANBUL’A İNTİKALİ - (:unkn) unknown (My University, 2019)
Mukaddes emanetler Hz. Peygamber’e, diğer Peygamberlere, âl-i Resûl’e, HulefaiRaşidin’e, sahabe-i kirama ve İslâm dininin önde gelen şahsiyetlerine ait eşyalardır.Bu emanetlerin bugün yaklaşık 605 parçası Topkapı Sarayı Müzesi’nde, diğerlerininbirkısmı da İstanbul’un muhtelif bölgelerinde muhafaza edilmektedir. Bunlarınİstanbul’a ne zaman ve nasıl getirildiği tam olarak ortaya konulmuş değildir. Bumakalede emanet-i mübarekenin Yavuz Sultan Selim’in Mısır seferinden 20. yüzyılakadar olan dönemde ne zaman ve nasıl İstanbul’a intikal ettikleri ele alınmıştır.Sancak-ı Resûl, Hırka-i Saadet, Hz. Osman’a isnad edilen Kur’an(lar) ve Kâbeanahtarları müstakil başlıklar hâlinde; diğer emanetler ise İstanbul’a getiriliştarihlerine göre incelendi. Bunun için konuyla ilgili kronikler ve arşiv malzemesindenistifade edildi. Özellikle Topkapı Sarayı Müzesi Arşivi’nde muhafaza edilenmüfredat defterlerinin konuyla ilgili önemli veriler sağladıkları ortaya konuldu. Ayrıcabugüne kadar müracaat edilmemiş olan bazı kaynakların mukaddes emanetlerinİstanbul’a getirilmesiyle ilgili yazılanları tamamen değiştirdiği tespit edildi.

Sacred relics are the things that belonged to the Prophet Muhammed, other prophets, prophet Muhammed’s family, Rashidun Caliphs, companions of the Prophet and other prominent figures of the Islamic religion. Today, approximately 605 pieces of these relics are kept in the Topkapı Palace Museum while others are preserved in various parts of Istanbul. When and how they were brought to Istanbul is not fully revealed. In this article, when and how the sacred relics were transferred in the period of time from the Selim I’s Egypt Expedition to the 20th century has been discussed. In this manner Sacred Standard of Muhammad, Khirka-yi Sa’adet, the Koran(s) that are said to have belonged to Uthman b. Affan and keys of Kaaba have been examined under seperate titles; the others have been examined according to their arrival dates. For this purpose, chronicles and archival material were used. In particular, it was revealed that the curriculum books kept in the Topkapı Palace Museum Archives provided important data on the subject. In addition, it has been determined that some of the resources that have not been considered so far have completely changed the writings on bringing the sacred relics to Istanbul.
“Relocatıon of The Holy Relıcs to Istanbul”
Keywords: Antropoloji